Regional genomic regulation of cardiac sodium–calcium exchanger by oestrogen - Chen, Guojun (Blackwell Science Inc, 2011)
Female rabbit hearts are more susceptible to torsade de pointes (TdP) in acquired long QT type 2 than males, in-part due to higher L-type Ca(2+) current (I(Ca,L)) at the base of the heart. In principle, higher Ca(2+) influx via I(Ca,L) should be balanced by higher efflux, perhaps mediated by parallel sex differences of sodium–calcium exchange (NCX) current (I(NCX)). We now show that NCX1, like Cav1.2α, is greater at the base of female than male left ventricular epicardium and greater at the base than at the apex in both sexes. In voltage-clamp studies, inward (0, +20 mV, P < 0.04) and outward (−80, −60, −40, −20 mV, P < 0.01) I(NCX) densities were significantly higher (1.5–2 fold) in female base compared to apex and male (base and apex) myocytes. Myocytes were incubated ±17β-oestradiol (E2 = 1 nm) and I(NCX) was measured on days 0, 1, 2 and 3. Inward and outward I(NCX) decreased over 2 days in female base myocytes becoming similar to I(NCX) at the apex. E2 incubation (24 h) increased NCX1 (50%) and I(NCX) (∼3-fold at 60 mV) in female base but not endocardium, apex or in male base myocytes. I(NCX) upregulation by E2 was blunted by an oestrogen receptor (ER) antagonist (fulvestrant, 1 μm), and inhibition of transcription (actinomycin D, 5 μg ml(−1)) or translation (cycloheximide, 20 μg ml(−1)). Dofetilide (an I(Kr) blocker) induced early afterdepolarizations (EADs) in female base myocytes cultured for 1 day if incubated with E2, but not without E2 or with E2+KB-R4973 (an I(NCX) inhibitor), E2+fulvestrant or E2 with apex myocytes. Thus, E2 upregulates NCX1 by a genomic mechanism mediated by ERs, and de novo mRNA and protein biosynthesis, in a sex- and region-dependent manner which contributes to the enhanced propensity to EADs and TdP in female hearts.